(3JaSjQ GdbQBfs - (3efUhQ Hf eMeO Hf YHO GdLHGQ GdSeYGfj GdTGaYj, CHh efUhQ , LeGd GdOjf J (B562 (3g` s
(3ChdgG (B:s
(3Chdg ShQI GdYfcHhJ(B: (3hgj ecjI ai bhd YWG hGdMSf heOfjI ai GMO bhd GHf YjGV s
(3BNQgG (B:s
(3ceG JQc cJGHI ShQI GdaGJMI hGddg CYde Je GdLRA GdKGdK s
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B449s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B(136) s
Keywords: (3GdJaSjQ hYdhe GdbQBfs